EFEK PEMANASAN TERHADAP KARAKTERISTIK DISTRIBUSI AMMONIA PADA ALIRAN GAS LAMINAR PADA SCR CATALYTIC FILTER DENGAN MENGGUNAKAN SIMULASI NUMERIK - Syaiful, Syaiful (ROTASI, 2010)
Selective catalytic reduction (SCR) and diesel particulat filter (DPF) as a combined systems are used to reduce NOx and soot emissions emitted by the diesel combustors, respectively. The use of these methods in automotive application requires more space. Accordingly, a SCR catalytic filter is devised NOx reacts with ammonia (as a reducing agent) at the certain temperatures through a catalyst producing a harmless matter. An optimal NOx conversion is influenced by several additional factors including the homogeneity of NH3/NOx mixture, catalyst temperature (reaction temperature), space velocity (velocity of exhaust gas), uniformity of flow and spraying quality of urea solution droplets. To control NOx emissions, the need for smooth gaseous flow distributions become more important. The most important of gaseous flow distributions is the distribution of ammonia and NOx entering the SCR catalyst with the actual NH3/NOx ratio being the most frequently specified parameter. In SCR application, the important thing is not only on NOx reduction but also on ammonia slip which is influenced by the ammonia distribution. A heating temperature is required to achieve a temperature window. However, the heating temperature affects the gaseous flow structure in SCR catalytic filter which influences the ammonia mass distribution. Therefore, the uniformity of flow with the effect of heating temperature is considered in this study. Two Reynolds numbers of 320 and 640 are imposed to investigate the ammonia mass distribution characteristics at the laminar flow. The heating temperature is imposed in the range from 473 to 1273 K with 200 K intervals.The results show that the uniformity of ammonia mass distribution indicated by the mixing index reduces as increasing the heating temperature at the laminar flow.http://ejournal.undip.ac.id/index.php/rotasi/article/view/1972/1731